2014
DOI: 10.1055/s-0034-1395794
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Pleural Access

Abstract: Ultrasonography of the thorax has become a more recognized tool in pulmonary medicine, thanks to continuing clinical research that has proven its many valuable roles in the day-to-day management of pulmonary and pleural diseases. Ultrasound examination is a cost-effective imaging modality that permits the pulmonologist to obtain information about the pathologies in the thorax without the risk of exposure to ionizing radiation, providing the examiner with real-time and immediate results. Its ease of use and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…As compared with the first reflection, subsequent reflections reach the transducer with a temporal delay and are erroneously interpreted and displayed as signals from deeper within the lung tissue. Consequently, the distance between the superimposed A-lines is always equidistant to or a multiple of the distance between the pleura and the transducer surface (Shojaee and Argento 2014;Saraogi 2015). Recurrent vertical hypoechoic spaces between A-line conglomerates are caused by ribs that do not allow for the ultrasound waves to penetrate further, generating a downward shadow in the ultrasound image (Villalba-Orero et al 2017).…”
Section: Lus In Healthy Lungsmentioning
confidence: 99%
“…As compared with the first reflection, subsequent reflections reach the transducer with a temporal delay and are erroneously interpreted and displayed as signals from deeper within the lung tissue. Consequently, the distance between the superimposed A-lines is always equidistant to or a multiple of the distance between the pleura and the transducer surface (Shojaee and Argento 2014;Saraogi 2015). Recurrent vertical hypoechoic spaces between A-line conglomerates are caused by ribs that do not allow for the ultrasound waves to penetrate further, generating a downward shadow in the ultrasound image (Villalba-Orero et al 2017).…”
Section: Lus In Healthy Lungsmentioning
confidence: 99%
“…Regarding the safety of VATS, and considering the risk of MACCE causing disabling and/or fatal outcomes after lung cancer surgery, we concluded that continuing aspirin is worthwhile because there were no differences in bleeding events, thrombotic events, and operative times between the aspirin group (group 2) and nonaspirin group (group 1). Ultrasound is a cost-effective imaging modality that permits clinicians to obtain information regarding the thorax without the risk of exposure to ionizing radiation, and it provides real-time and immediate results (23). Because it is easy to use, easy to learn how to use it, portable, and accurate when examining the pleural space, it has allowed for safer pleural procedures, including VATS.…”
Section: Adhesions Predictedmentioning
confidence: 99%
“…A thorough US study can easily define the precise tumor localization (extrapleural, pleural or parenchymal), the local infiltration, the mass extent and its nature (solid, cystic or complex) . Thoracic US can also guide transthoracic biopsy of pleural tumors if an appropriate and safe window is identified …”
Section: Chest Ultrasound Findingsmentioning
confidence: 99%